Peran Leadership dalam Meningkatkan Motivasi Karyawan pada Salon Arabela Beauty Salon di Kab. Sikka - Kristin Sujila; Egenia Mauritsia; Maria Suanti Nena; Anamarian Ellyria D’Nisa; Putri Ariyani Widyastuti (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This study aims to analyze the critical role of leadership in improving employee motivation at Arabela Beauty Salon in Sikka Regency. The problems identified include employees who still lack enthusiasm in their work, low discipline, and limited initiative in providing service to customers, which affects overall service quality. This research employs a descriptive qualitative approach, using data collection techniques such as interviews, observations, and documentation. The results indicate that leadership at Arabela Beauty Salon plays a significant role in enhancing employee motivation by providing clear direction, maintaining open communication, and offering attention as well as support to employees. However, the reward system and performance evaluation processes still need improvement to further encourage employees in achieving optimal service targets and high-quality outcomes. Thus, the application of an effective, participative leadership style can significantly improve employee motivation, which in turn leads to better service delivery and increased customer satisfaction.